Embrace(D) : a promotional campaign to raise awareness of depression among Singapore youth - Goh, Eunice Yi Hui (2015)
Embrace(D) is a social campaign aimed at raising awareness of depression amongst youths in Singapore. Conceptualised and executed by four final year undergraduates of the Wee Kim Wee School of Communication and Information at Nanyang Technological University, the campaign strives to create a supportive environment where sufferers of depression feel encouraged to seek help. The campaign targeted young people aged 18-25, an age group that represents the most at-risk group of developing depression. As a result, the campaign’s strategy was focused on using youth-centric approaches which included utilizing social media platforms to communicate campaign messages, organising on-ground initiatives at tertiary institutions and youth hubs like *SCAPE, and incorporating interactive elements into the roving exhibition. Through the campaign, the team hopes to provide opportunities for our target audience to know more about depression and the ways they, as friends and family members, can help their loved ones who may be suffering from depression. This report seeks to provide insights to the primary and secondary research conducted and its key findings that helped shape the campaign strategies. Details surrounding the campaign conceptualisation and execution will also be presented and discussed. Additionally, in order to assess the success of the campaign, pre-campaign and post-campaign surveys were analysed and compared alongside the review of both input and output objectives. Finally, limitations of the campaign were discussed, and recommendations were made to act as learning points for future campaigns of similar nature. This report also includes transcripts, collateral designs, diagrams and other original documents in its appendices that act as references to the main body of text.